A Congestion Controlling Mechanism Using Smart Self Divisional Congestion Node Window (SSDCNW) And Traffic Analysis For VANET (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicular ad hoc networks are a very common area of study in which research work is carried out on different issues, such as end-to-end data routing without loss. Routing is a very tedious activity in this network because the place of vehicles is always changed location-wise. In this paper, we propose a Smart Self Divisional Congestion Node window (SSDCNW) for minimizing the congestion window size and provide the data rates of the protocol used for Jaipur and Kota city in Vanet. In WAVE/ IEEE 802.11p vehicular ad hoc networks, we studied the mechanism of transmission packets over the control channel. The findings of the simulations carried out in a practical environment justify our theoretical considerations and confirm our protocol's feasibility and effectiveness by demonstrating substantial changes in network efficiency. We analyzed the performance of the system for 2 general scenarios. With the NS-3 simulator and SUMO, we performed detailed simulation operations to find the effect of our proposed SSDCNW technique to forecast data rates and reduce and controlling the congestion level. A rise in packet processing time does not have a significant effect on network efficiency for most messages; on the contrary, it is significant for messages to arrive correctly.